EFEKTIVITAS STAR AMBASSADOR TWICE DALAM KEPUTUSAN PEMBELIAN PRODUK SCARLETT WHITENING OLEH FOLLOWER TWITTER @TWICE_INDONESIA - Achmad Dika Prasetyo (2022)
In the current information age, humans live side by side with sophisticated technology that is used to help the needs of human activity, namely the internet, because the internet makes it easy to enter and leave culture from outside. the current trend that is felt is the Korean Wave phenomenon, this trend makes many people enjoy Korean culture, so many products from Indonesia are competing to invite Korean artists, one of which is Indonesian skincare companies that compete by using Korean artists and idols as brand ambassadors, This makes it common when Indonesian products invite Korean artists, are they still effective and there are many controversies such as when TWICE became Scarlett Whitening's star ambassador, whether this affects purchasing decisions, The research method used is quantitative and uses an explanatory method approach, technical the data used through a survey with the object of Twitter Followers @TWICE_Indonesia by taking a sample of 100 people, the results of this study obtained a coefficient value of 0.538 which means that it has a moderate correlation and the correlation coefficient is positive, then the results of u If the coefficient of determination is 21.7%, it means that the variable x has an effect on the variable Y and the result of the t-test is 5.204 and it means that the t count is t tabek, therefore HO is rejected and ha is accepted.